The role of artificial intelligence in enhancing Lecturer professional development and performance management - Yanthy Herawati; Ajat Ajat; Magito Magito; Ibnu Haris Nasution; Rahmat Rahmat (Journal of Educational Management and Instruction (JEMIN), 2025)
The integration of Artificial Intelligence (AI) in education, particularly for teacher professional development, has gained attention in recent years. However, its application in assessing lecturer performance and fostering growth remains underexplored, especially in developing countries like Indonesia. This study aimed to investigate how AI can enhance lecturer performance assessment and support personalized professional development, with a specific focus on higher education level. An exploratory case study design was employed, involving 15 lecturers teaching at several universities in Jakarta and two policymakers. Data were collected through semi-structured interviews and focus group discussions, and analyzed using Miles and Huberman's qualitative data analysis methods. The findings revealed that AI tools, such as Socrative, Edthena, and Teacher Advisor with Watson, were effective in providing personalized feedback and performance assessments, which led to improved lecturer knowledge and classroom effectiveness. However, challenges such as resistance to change, inadequate infrastructure, and data privacy concerns were identified as significant barriers to AI adoption. The study concludes that AI has great potential to enhance teacher development but requires systemic support, including infrastructure, training, and clear data management policies. The findings suggest that AI can significantly improve teaching practices if integrated thoughtfully and equitably across educational institutions. These insights contribute to the growing discourse on digital transformation in education by offering practical implications for policymakers and institutions aiming to leverage AI for faculty development.